Chemical Changes in Leaves of Corn and Bean Plants Exposed to Simulated Acid Rain - Ozkaya, Ahmet; Ciftci, Harun; Yilmaz, Okkes; Cil, Erol; Basar, Salih (Chem Soc Pakistan, 2012)
In this study, the effects of simulated acid rain on vitamin E, vitamin D-2 and fatty acids levels of corn and bean leaves were investigated. It was determined that the level of palmitoleic acid (C16:1) increased in comparison with the control group (p<0.01, p<0.05), while the vitamin E, D-2 and linoleic acid (C18:2) levels considerably decreased in comparison with the control group (p<0.001). From the these results, we can suggest that simulated acid rain can have negative effects on levels of fatty acids, vitamin E and vitamin D-2 of these plant leaves.
Keywords: Simulated acid rain; Fatty Acids; Vitamins E and D-2; corn; bean; leaf